(untitled) (LEARNing Landscapes, 2019)
Learning to conduct qualitative research is a complex endeavor. In this article, I introduce mixed reality simulations as a scaffolded learning tool to support student mastery of learning and knowing how to conduct qualitative research. Like flight simulators used to train airline pilots prior to flying an actual airplane, mixed reality simulations provide active practice opportunities to interact with avatars in order to practice newly learned skills. I discuss this in the context of my experiences using mixed reality in an undergraduate youth participatory action research methods course as a scaffold before joining research teams with high-school-aged coresearchers.